2021
DOI: 10.1139/cjp-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

Phonon polaritons in magnetoelectric multiferroics film: the possibility to drive surface modes using magnetic field

Abstract: In this paper, we report our numerical study of transverse mode phonon polaritons generated on magnetoelectric multiferroic films. The mathematical models of the dispersion relation for both surface and guided-wave modes were derived by solving the Maxwell equations. Then, numerical calculations were performed for various thicknesses using parameters suitable for illustrating magnetoelectric multiferroic BaMnF4. It was found that around the thicknesses of 0.1 mm–1 mm, the guided-wave modes were discreet. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Here, we used the dielectric thickness 0.35 cm and damping cm. The trend of the calculated ATR in this paper (figure 2a) was similar to the trend of the ATR spectroscopy from the previous studies (Jensen, 1997;Gunawan, 2021). The dip in ATR spectroscopy was related to the intersection between ATR line and dispersion relation curve curve (see figure 2b).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we used the dielectric thickness 0.35 cm and damping cm. The trend of the calculated ATR in this paper (figure 2a) was similar to the trend of the ATR spectroscopy from the previous studies (Jensen, 1997;Gunawan, 2021). The dip in ATR spectroscopy was related to the intersection between ATR line and dispersion relation curve curve (see figure 2b).…”
Section: Resultssupporting
confidence: 89%
“…The reciprocal property of surface polaritons on the surface of semi-infinite multiferroics was shown in ATR spectroscopy (Gunawan et al, 2011). The existence of surface polaritons on multiferroic film were also predicted numerically using calculated ATR (Gunawan et al, 2017;Gunawan et al, 2021). The ATR spectroscopy was obtained by measuring the ATR reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these dips predicted the possibility to excite surface plasmon which then generating surface plasmon polaritons at the interface between metal and fatty acid. The results in figure 2 also showed that the trend of the curvatures similar to the shape of calculated ATR spectroscopy from the previous studies (Jensen, 1997;Gunawan, 2021). These SPR was significantly affected by metal since it had the role as active material to provide the free charges.…”
Section: Resultssupporting
confidence: 78%
“…Using this method, the existence of surface plasmon excitation was shown by a sharp decrease in ATR spectroscopy. The ATR had successfully used in the studies of surface plasmons excitation in various materials, such as: dielectrics (Borstel et al, 1974 ;Torii et al, 2000), magnetics (Jensen et al, 1995;Jensen et al,1997) and also magnetoelectric multiferroics (Gunawan et al, 2011;Gunawan et al, 2017;Gunawan et al, 2021). The ATR can also be performed numerically by calculating the ATR reflection.…”
Section: Introductionmentioning
confidence: 99%